Audit Sistem Informasi Pelayanan Perpustakaan Binjai Menggunakan Framework Cobit 5 - Yulia Ningsih; Siti Alyunita Mega Lestari; Indah Kelana Sari; Shela Andini (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
The Binjai Library has developed a technology-based information service system to improve service quality for the community. This study aims to audit the information service system of the Binjai Library using the COBIT 5 framework. Based on the analysis, it was found that the information system has not reached the expected target levels in all domains. The average maturity level calculation shows a score of 1.43 or 143%, which is classified as Fully Achieved. Key findings include the near alignment of human resources and IT capabilities with institutional needs, suboptimal innovation in services, and the need for improvement in HR management and communication. This study concludes that the Binjai Library needs to implement improvements and innovations to enhance the performance of the information system and service quality.